Skrining Fitokimia dan Uji Aktivitas Antibakteri Ekstrak Etanol Dedak Padi (Oryza sativa L.) terhadap Kebocoran Membran Bakteri Staphylococcus aureus - Auza , Maharani; Nasution , Haris Munandar; Pulungan , Ainil Fithri; Rani , Zulmai (Journal of Pharmaceutical and Sciences, 2025)
Background: Rice bran is commonly utilized only as animal feed and is often regarded as a byproduct of rice milling. However, rice bran contains flavonoid compounds that exhibit antibacterial activity. This study aims to explore the potential of rice bran as an antibacterial agent, specifically against Staphylococcus aureus, through antibacterial activity testing and analysis of cell membrane leakage mechanisms. Objective: This research aims to utilize rice bran by evaluating its antibacterial activity and its mechanism of bacterial membrane leakage against Staphylococcus aureus. Methods: This experimental study involved the collection of rice bran samples, plant determination, simplicia characterization, and extraction using maceration with 96% ethanol. Phytochemical screening was conducted to identify active compounds, while antibacterial activity was tested using the disk diffusion method (Kirby-Bauer) at concentrations of 10%, 12.5%, 25%, 50%, 70%, and 80%. The membrane leakage mechanism was assessed by measuring nucleic acid and protein leakage (UV-Vis spectrophotometry) as well as Ca²⁺ and K⁺ ion release (atomic absorption spectrophotometry, AAS). Data were statistically analyzed using SPSS. Results: The ethanolic extract of rice bran yielded a 26.38% extraction yield and contained secondary metabolites, including alkaloids, flavonoids, tannins, saponins, triterpenoids/steroids, and glycosides. The antibacterial assay revealed inhibition zones classified as strong activity. Furthermore, rice bran extract induced membrane leakage in S. aureus, evidenced by increased mean absorbance values and standard deviations for DNA, protein (UV-Vis spectrophotometry), and Ca²⁺ and K⁺ ions (atomic absorption spectrophotometry) with rising extract concentrations. Conclusion: Rice bran exhibits potential as an antibacterial agent against Staphylococcus aureus through a membrane leakage mechanism. These findings support the utilization of rice bran not only as animal feed but also as a source of bioactive antimicrobial compounds.